Frequency of H. Pylori in Patients of Dyspepsia Through Biopsy Assessment (Journal of Fatima Jinnah Medical University, 2018)
Background: Various problems like gastritis, gastric ulcer, duodenal ulcer and non-ulcer dyspepsia are commonly caused by Helicobacter Pylori. Less developed countries like Pakistan, India and Bangladesh are more prone to this infection as compared to more developed countries as Japan. The infection rate in Pakistan, stating specifically, has been reported to be as high as 90% in adult Pakistani population. Therefore, diagnosis and subsequent eradication of H. pylori may lead to a reduction in morbidity as well as mortality. Objectives: To determine the frequency of + ve biopsy for presence of H. Pylori when taken from various biopsy sites in patient with dyspepsia. Methodology: This cross-sectional study was conducted in the department of Gastroenterology & Hepatology, Shaikh Zayed Hospital Lahore. Seventy five patients of dyspepsia were included who were evaluated for initial history and clinical examination. The upper GI endoscopy was performed and biopsies from corpus, antrum and fundus were taken. The data were entered and analyzed using SPSS version 17.0 to demonstrate descriptive statistics through frequency, percentages, mean, SD etc. Results: Out of total 75 patients, 30 male (40%) and 45 (60%) females having mean age of 37.4 years were reported. H. Pylori was detected in biopsy of 35 patients (46%) in fundus, in body of 29 patients (38.7%), and 35 patients had H. Pylori (46%) in antrum. Conclusion: The presence of H. Pylori infection is frequently found in patients of dyspepsia especially in biopsy site of fundus and body.
Keywords: Dyspepsia, biopsy site, antrum, body, fundus, H.Pylori, Endoscopy